Metabolic responses and mechanisms during water immersion running and exercise - Frangolias, D. D.; Rhodes, E. C. (Sports Medicine, 1996)
The low impact nature of exercise in the water has increased interest in this form of exercise and specifically in water running as a cross-training modality. It is used as a possible preventative and therapeutic modality for rehabilitation. The high impact nature of land running predisposes the runner to stress of the lower limbs and overuse injuries. The need to reduce impact, as well as provide a low impact or non-weight-bearing condition for rehabilitation, has led runners and their coaches to the water. This increased interest by coaches and their athletes, attending sports medicine physicians and rehabilitative professionals has stimulated research into water immersion to the neck (WI) running. Exercise in the water has long been used by rehabilitative professionals with patients who have physically debilitating conditions (i.e. arthritis, musculoskeletal disorders) as it provides a medium for even those with limited mobility to exercise and relax their muscles. Numerous comparative studies into WI running from a metabolic as well as a training perspective have been published. WI has also long been used to simulate weightlessness for the comparative study of cardiorespiratory function and thermoregulation. WI and the associated cephalad shift in blood volume has implications on exercise responses during WI running exercise. In addition, the non-weight-bearing nature of WI running also raises issues of the cross-training benefits of WI running. WI running style and prior familiarity with the activity have been found to have a direct relationship with the comparability of WI to land running. This review presents current research into WI running, training specificity and comparative physiology.